EXPERIENCE OF CETIRIZINE SYRUP APPLICATION IN THE ATOPIC ECZEMA IN CHILDREN - F.Ch. Shakhtakhtinskaya (Union of pediatricians of Russia, 2008)
This article demonstrates the results of the scientific research, whose purpose was to study the impact of cetirizine syrup on the course of atopic eczema among 36 children (2-6 years old). The study shows that introduction of the medication in the complex therapy of atopic eczema in children provides a fast clinical effect. Cetirizine syrup is well tolerated by the children.Key words: atopic eczema, children, treatment.